Influences of the shoe sole hardness and speed on stride frequency and striking position variability during treadmill running without awareness of speed change - Teng, P. P.; Kung, H. M.; Chiu, H. T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to investigate the influences of wearing soft or hard soled shoe on the runner`s stride frequency and striking position variability, while the runner was not aware of the treadmill speed changing by visual or auditory information. The positions of the right ankle markers on the twenty subjects were captured to determine the stride frequency and striking position variability from ten strides at different speeds during six minutes of treadmill running. The results showed that the runner`s stride frequency significantly increased as the treadmill speed increased (p<0.05). However, sole hardness did not significantly affect the stride frequency under the four different speed conditions. Furthermore, the shoe sole hardness and speed seemed to have no influences on the striking position variability in this study.